Integration of physics learning content in the context of automatic machine design of fish feed throwers based on solar cells arduino IoT system - Rendy Wikrama Wardana; Yestilia Anggraini; M. Lutfi Firdaus; Fitri April Yanti; Elsi Adelia Fitri (Momentum: Physics Education Journal, 2024)
The utilization of aquaculture, especially in freshwater fish farming potential, is still not optimal. In general, fish feeding is still done manually and depends on human resources which is done simply. So an automatic fish feed thrower based on solar cells was designed to minimize the risk of delays in feeding fish. This innovation can be integrated in learning where it is adapted to physics content. This research uses a mix of methods with data collection techniques in the form of observations related to the surrounding environment and the learning process, documentation in the form of learning tools such as syllabus, lesson plans, curriculum, documentation, questionnaires, testing feed machine tools and literature studies. This research instrument is in the form of descriptive observation sheets, observation analysis sheets testing feed machine tools. Analytical techniques in this study use descriptive, qualitative and quantitative analysis techniques. The results of this research are in the form of content integration in physics learning in the context of designing a solar cell-based automatic fish feed throwing machine consisting of 6 physics contents that are adapted to the context of solar cell-based automatic fish feed throwing machines. The results of this study show that the application of the use of an automatic machine for throwing fish feed based on solar cells can be used as a source of learning, especially in physics subjects.